2020
DOI: 10.1002/app.50094
|View full text |Cite
|
Sign up to set email alerts
|

Wear and thermal behavior of basalt fiber reinforced rice husk/polyvinyl chloride composites

Abstract: Plant fiber reinforced polymer composites (PFRPs) in practical application are often subjected to both complex friction and variable temperature environments. The present work explores the possibility of reinforcing rice husk/polyvinyl chloride (RH/PVC) composites with basalt fibers (BF) for developing a new wear resistant material with improved thermal stability. The results showed that the structural strength and wear resistance of the composites increased at first and then decreased with an increasing ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The thermogram of the B/PP, J/PP, and pure PP showed a progressive weight loss as the temperature increased. The composite samples degraded in two phases: they became brittle and then they crumbled [ 31 ]. A progressive two stage thermal degradation occurred: the first stage is the degradation of the matrix, and the second stage is the degradation of fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The thermogram of the B/PP, J/PP, and pure PP showed a progressive weight loss as the temperature increased. The composite samples degraded in two phases: they became brittle and then they crumbled [ 31 ]. A progressive two stage thermal degradation occurred: the first stage is the degradation of the matrix, and the second stage is the degradation of fibers.…”
Section: Resultsmentioning
confidence: 99%
“…The composite samples in which the A1 2 O 3 particles were closely packed had an external surface polymer that inhibited particle‐supported reinforcement. [ 29 ] Consequently, although the ability of the composite samples to resist damage under the action of impact forces strengthened, the hardness of the composite samples decreased.…”
Section: Resultsmentioning
confidence: 99%
“…The use of coupling agents, as studied by Raghu [ 24 ], showed that the impact strength of RH–PP composites decreased with increasing filler loadings. Jiang et al [ 41 ] explored the possibility of reinforcing RH–PVC composites with basalt fibers (BF) and found a noticeably increase in impact strength, whereby the BF acted as a reinforcing agent and strengthened the mobility of the matrix chains. Additionally, the aspect ratio of BF was higher than RH, thus the shift of the stress from the matrix to the fiber was more effective.…”
Section: Impact Strength Of Rh Compositesmentioning
confidence: 99%